Causal Factors Affecting Organizational Health of Local Administrative Organizations in the Southern Part of Thailand - U-senyang, Sarannee; Trichandhara, Khanon; Rinthaisong, Idsaratt (WMS Journal of Management, 2017)
The objective of this survey research was to investigate causal factors affecting organizational health of local administrative organizations in the Southern part of Thailand. The population consisted of 1,176 local administrative organizations in the Southern part, and 600 organizations were selected as a sample group through proportional stratified random sampling. Data were collected using a questionnaire and analyzed using structural equation modelling (SEM). The study found that the causal relationship model affecting organizational health of local administrative organizations in the Southern part of Thailand was well fitted to empirical data (/df = 4.874, RMSEA = 0.080, CFI = 0.930, SRMR = 0.047). When considering causal factors, it was found that organizational commitment had direct positive influence on organizational health while organizational justice had direct negative influence on organizational health and direct positive influence on organizational commitment. Organizational culture had direct positive influence on organizational health, and transformational leadership had direct positive influence on the organizational health, direct positive influence on organizational culture, direct positive influence on organizational commitment, and direct positive influence on organizational justice.